Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

please help

1: Find the product of -3x3 + 2x – 4 and 3x – 2

2: Is the product of -3x3 + 2x – 4 and 3x – 2 equal to the product of -3x3 + 2x – 4 and 2x-3?


Sagot :

Step-by-step explanation:

multiplying expressions.

remember every term of one expression has to be multiplied with every term of the other expression, and the results are added up (while considering their individual signs, of course).

1.

(-3×3 + 2x - 4)(3x - 2)

(-9 + 2x - 4)(3x - 2)

(-13 + 2x)(3x - 2) = -13×3x + -13×-2 + 2x×3x + 2x×-2 =

= -39x + 26 + 6x² - 4x = 6x² - 43x + 26

2.

let's do the other multiplication and compare the result with the result of 1 :

(-13 + 2x)(2x - 3) = -13×2x + -13×-3 + 2x×2x + 2x×-3 =

= -26x + 39 + 4x² - 6x = 4x² - 32x + 39

no, this product is not the same as in 1.